Principles of Ownership and Distribution of Mining Products in the Perspective of Islamic Law: A Historical Review of the Time of the Prophet Muhammad SAW - Khotim, Ahmad (Sekolah Tinggi Agama Islam At-Tahdzib Jombang, 2025)
This study examines the ownership and management of mines during the era of the Prophet Muhammad SAW. The method used in this study is qualitative by analyzing literature from Islamic historical sources, such as book documents, articles published in journals, texts of verses and hadiths of Islamic teachings, and others. The findings of this study indicate that the Prophet Muhammad SAW established basic steps in natural resource management, including mining, which are based on the principles of justice, benefits for society, and environmental protection. The summary of this study is that the mining management policy during the time of the Prophet Muhammad SAW can be a reference in sustainable and fair natural resource management today.